2013
DOI: 10.1016/j.celrep.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

ADAR Regulates RNA Editing, Transcript Stability, and Gene Expression

Abstract: SUMMARY Adenosine deaminases acting on RNA (ADARs) convert adenosine to inosine, which is then recognized as guanosine. To study the role of ADAR proteins in RNA editing and gene regulation, we sequenced and compared the DNA and RNA of human B cells. Then, we followed up the findings experimentally with siRNA knockdown and RNA and protein immunoprecipitations. The results uncovered over 60,000 A-to-G editing sites and several thousand genes whose expression levels are influenced by ADARs. Of these ADAR targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
194
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(209 citation statements)
references
References 53 publications
13
194
2
Order By: Relevance
“…As one might predict, editing has been shown to influence splicing (Agrawal and Stormo, 2005;Bratt and Ohman, 2003;Jin et al, 2007;Laurencikiene et al, 2006;Lev-Maor et al, 2008;Rueter et al, 1999;Ryman et al, 2007;Solomon et al, 2013) and mRNA stability (Chen and Carmichael, 2012;DeCerbo and Carmichael, 2005;Wang et al, 2013). It is reasonable to assume, therefore, that editing affects most RNA processing pathways.…”
Section: Adars Do Much More Than Alter Codonsmentioning
confidence: 99%
“…As one might predict, editing has been shown to influence splicing (Agrawal and Stormo, 2005;Bratt and Ohman, 2003;Jin et al, 2007;Laurencikiene et al, 2006;Lev-Maor et al, 2008;Rueter et al, 1999;Ryman et al, 2007;Solomon et al, 2013) and mRNA stability (Chen and Carmichael, 2012;DeCerbo and Carmichael, 2005;Wang et al, 2013). It is reasonable to assume, therefore, that editing affects most RNA processing pathways.…”
Section: Adars Do Much More Than Alter Codonsmentioning
confidence: 99%
“…In this study we sought to examine whether the editing of target mRNA, rather than miRNA, might affect mRNA:miRNA binding by altering seed matches. The possibility that miRNA target sites can be created or deleted by RNA editing has been proposed (23,28), but studies supporting this hypothesis are very limited (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…We find that ADAR interacts with mRNAs encoding transcriptional regulators, zinc-finger proteins, and components of the secretory pathway. A similar approach has been taken to identify ADAR substrates in human B cells (Wang et al 2013), and the results indicate that human ADAR1 also targets mRNAs encoding zinc-finger proteins. It is remarkable that Xenopus and human ADAR target similar classes of mRNAs, as the vast majority of Ato-I editing events in the human transcriptome occur in primate-specific Alu elements, which are absent in frogs.…”
Section: Adar-endornps: Adar-rnps Containing Endogenous Rnasmentioning
confidence: 99%
“…We find that the ADAR-associated mRNAs are enriched for transcripts encoding transcriptional regulators, zinc-finger proteins, and components of the secretory pathway (Supplemental Table 2). It has been demonstrated that editing targets in human B cells are also enriched for mRNAs encoding zinc-finger proteins (Wang et al 2013), suggesting that ADAR plays a conserved role in regulating this class of mRNAs. The finding that ADAR-associated mRNAs tend to encode transcription factors and proteins involved in signal transduction led us to hypothesize that ADAR might sequester and translationally repress maternal transcripts needed later in development.…”
Section: Adar Associates With Endogenous Xenopus Mrnasmentioning
confidence: 99%